2021
DOI: 10.18415/ijmmu.v8i7.2836
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Based Learning Integration in Stem Education to Improve Environmental Literation

Abstract: This study aims to see the integration of problem-based learning in STEM education can improve the environmental literacy of elementary education students. The research is qualitative and uses the literature study method. Searching journals from the Science Direct search engine, Science Education Journal, ERIC, Google search engine, and others with the keywords Problem-Based Learning, Science, Technology, Engineering and Mathematics (STEM), environmental literacy, scientific literacy resulted in 3,298 journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Some other similar studies, among them Widowati et al, (2021) with the research title Problem-Based Learning with Science, Technology, Engineering, and Mathematics (STEM) Approach to Improve Critical Thinking Skills and Conceptual Understanding of Junior High School Students indicate improvement in the critical thinking skills of high category students (N-Gain value is70.78%). The application of PBL STEM can increase concept acquisition with an N-Gain value of 69.56%.…”
Section: Resultsmentioning
confidence: 98%
“…Some other similar studies, among them Widowati et al, (2021) with the research title Problem-Based Learning with Science, Technology, Engineering, and Mathematics (STEM) Approach to Improve Critical Thinking Skills and Conceptual Understanding of Junior High School Students indicate improvement in the critical thinking skills of high category students (N-Gain value is70.78%). The application of PBL STEM can increase concept acquisition with an N-Gain value of 69.56%.…”
Section: Resultsmentioning
confidence: 98%
“…The learning process applied gives the impression of a flexible process for students. The pre-service teacher has designed the best possible way to solve life's problems in the material being taught by finding solutions (Widowati et al, 2021). This was done in research on ecological material with the existence of 3D miniatures which were assembled by students with simple tools and materials and material for environmental change and preservation by making simple filter tools and comparison tools for pollution causes.…”
Section: Resultsmentioning
confidence: 99%
“…PBL implementation uses information and communication technology (ICT) generates better content for teaching materials and skills than teachers (Belagra & Draoui, 2018;Yuliansyah & Ayu, 2021). Previous studies found positive results in the ecological literacy skills of students using subject specific pedagogy and PBL (Riyadi, Prayitno, & Karyanto, 2018;Widowati, Purwanto, & Akbar, 2021). Similar studies found positive results in increasing students' digital literacy using PBL with online laboratory simulation (Perdana, Jumadi, Rosana, & Riwayani, 2020;Yustina, Mahadi, Daryanes, Alimin, & Nengsih, 2022).…”
Section: Introductionmentioning
confidence: 95%